Single event effects sensitivity of low energy proton in Xilinx Zynq-7010 system-on chip. (April 2017) - Du, Xuecheng; Liu, Shuhuan; Luo, Dongyang; Zhang, Yao; Du, Xiaozhi; He, Chaohui; Ren, Xiaotang; Yang, Weitao; Yuan, Yuan
Abstract: In this paper, experimental methods are emphatically described for measuring the proton single event effects (SEE) in Xilinx Zynq-7010 system-on chip. Experimental data are presented showing that low energy (3 MeV ≤ Energy ≤ 10 MeV) proton irradiation can cause single event effects in different hardware blocks of Xilinx Zynq-7010 SoC, including D-Cache, programmable logic (PL), arithmetic logical unit (ALU), float point unit (FPU) and direct memory access (DMA). Moreover, the sensitivities of different hardware blocks to single event effects are different. Finally, the Stopping and Range of Ions in Matter (SRIM) software calculations show the possible reasons for this difference. Highlights: Investigate the single event effects sensitivity of Xilinx Zynq-7010 SoC by the low-energy protons Describes the dynamic testing methods for different blocks of Zynq-7010 SoC in detail Obtain the SEE cross section curve for different energy protons